Quality Comparison of Dynamic Auditory Virtual-Reality Simulation Approaches of Approaching Vehicles Regarding Perceptual Behavior and Psychoacoustic Values - Jonas Krautwurm; Daniel Oberfeld-Twistel; Thirsa Huisman; Maria Mareen Maravich; Ercan Altinsoy (Acoustics)
Traffic safety experiments are often conducted in virtual environments in order to avoid dangerous situations and conduct the experiments more cost-efficiently. This means that attention must be paid to the fidelity of the traffic scenario reproduction, because the pedestrians’ judgments have to be close to reality. To understand behavior in relation to the prevailing audio rendering systems better, a listening test was conducted which focused on perceptual differences between simulation and playback methods. Six vehicle driving-by-scenes were presented using two different simulation methods and three different playback methods, and binaural recordings from the test track acquired during the recordings of the vehicle sound sources for the simulation were additionally incorporated. Each vehicle driving-by-scene was characterized by different vehicle types and different speeds. Participants rated six attributes of the perceptual dimensions: “timbral balance”, “naturalness”, “room-related”, “source localization”, “loudness” and “speed perception”. While the ratings showed a high degree of similarity among the ratings of the sound attributes in the different reproduction systems, there were minor differences in the speed and loudness estimations and the different perceptions of brightness stood out. A comparison of the loudness ratings in the scenes featuring electric and combustion-engine vehicles highlights the issue of reduced detection abilities with regard to the former.